Analisis Pengaruh Kurs Rupiah, Tingkat Suku Bunga, ROE dan DER terhadap Harga Saham Perusahaan Indeks IDX30 Periode 2014 – 2022 - Muhammad Ridwan Aditya; Marseto Marseto; Sishadiyati Sishadiyati (Syntax Corporation Indonesia, 2024)
This study aims to understand whether factors such as the Rupiah exchange rate, interest rates, Return on Equity (ROE) and Debt to Equity Ratio (DER) influence share prices of IDX30 companies from 2014 to 2022. Companies in the IDX30 index span the period 2014 - 2022 is the object of this study. For this study, 14 companies were selected as research samples through a purposive sampling method. This research applies secondary data with documentation techniques for data collection. Data analysis was carried out using the Eviews 10.0 analysis tool for panel data regression. The findings in the study explain that partially Rupiah exchange rate and ROE variables have a positive and significant influence on stock prices, the DER variable has a negative and significant influence on share prices, while interest rates have no impact on share prices. Simultaneously, share prices are influenced by the Rupiah exchange rate, interest rates, Return on Equity and Debt to Equity Ratio.